Road collisions as a cause of traumatic spinal cord injury in Ireland, 2001-2010 - COMISKEY, CATHERINE (My University, 2014)
Background: Road collisions remain the leading cause of traumatic spinal cord injury (TSCI) in the world. Half of all TSCIs in Ireland in 2000 were caused by road collisions. Since then, there has been a downward trend in road fatalities coincident with implemented road safety strategies. Objective: To examine the incidence of TSCI resulting from road collisions from 2001 to 2010. Method: This is a retrospective study using the hospital inpatient enquiry database of the tertiary referral center, which houses the national spinal injuries unit. Information retrieved included total numbers of patients with TSCI and number of TSCIs due to road collisions from 2001 through 2010, age groups affected, and the gender balance. Results: Over the 10-year period studied, the incidence rate of TSCI due to road collisions declined, although this did not reach statistical significance. The largest numbers of all TSCIs and TSCIs due to road collisions were in the 20- to 29-year age category and the male gender. Conclusions: As mortality due to road collisions declined, so did the number of TSCIs from the same etiology. An impactful road safety campaign is likely to have influenced these trends.
PUBLISHED
Keywords: epidemiology, road collisions, road safety, traumatic spinal cord injury; epidemiology, road collisions, road safety, traumatic spinal cord injury